Auctions, Market Prices and the Risk Attitude Effect - Maarten C.W. Janssen; Vladimir A. Karamychev (Tinbergen Institute, 2005)
This paper develops one possible argument why auctioning licenses to op-erate in an aftermarket may lead to higher prices in the aftermarket comparedto a more random allocation mechanism. Key ingredients in the argumentare differences in firms' risk attitudes and the fact that future market prof-its are uncertain so that winning an auction is like winning a lottery ticket.li one license is auctioned, auctions select the firm that is least risk averse.This is what we call the risk attitude effect. Firms that are less risk aversetend to set higher prices (or higher quantities in case quantity is the decisionvariable) in the marketplace than an average firm. When multiple licensesare auctioned, this conclusion gets strengthened when there is a differenti-ated Eertrand oligopoly in the marketplace. In case of Cournot competition,a strategic effect works against the risk attitude effect so that under certainconditions the more risk averse firms will be selected leading (again) to highermarket prices.
Keywords: D43; D44; D82; 330; Auctions; Risk Attitude; Aftermarkets; Auktion; Lizenz; Risikopräferenz